Adsorption mechanism of the environmentally friendly insulating gas C5F10O and its main decomposition products on a Cu (1 1 1) surface. (26th January 2021) - Zeng, Fuping; Feng, Xiaoxuan; Lei, Zhicheng; Wu, Siying; She, Congdong; Miao, Yulong; Zhang, Shiling; Tang, Ju
Abstract: The perfluoroketone C5 F10 O, not only has good environmental compatibility, but also has excellent insulation properties and has the potential to replace SF6 in medium and low voltage switchgear. This paper focuses on the compatibility of C5 F10 O and its main decomposition products with the copper material inside the equipment and specifically constructs several adsorption models of C5 F10 O and its main decomposition products on a Cu (1 1 1) surface. The adsorption mechanism was studied from a system structure, electron density distribution and density of states perspective. The results showed that C5 F10 O mainly adsorbed chemically on the Cu surface through carbonyl oxygen atoms. Its maximum adsorption energy is −24.48 kcal mol −1, with electrons transferring from the copper surface to the adsorbed oxygen atom; and the adsorption energies of the main breakdown products CF4, C2 F6, C3 F8, C3 F6, CF2 O, C2 F4 O and CO2 with the surface are all less than −9.56 kcal mol −1 . There is no obvious electron transfer between these decomposition gases and the copper surface, and thus, they belong to physical adsorption; while the adsorption energies of C3 F6 O, C2 F4 and CO in the top, bridge and Hcc sites are respectively −9.661 kcal mol −1, −14.651 kcal mol −1 and −25.489 kcal mol −1, electrons on the copper surface transfer to the oxygen atom of C3 F6 O and carbon atoms of C2 F4 and CO, forming stable chemical bonds, which belong to chemical adsorption. Through further analysis of the electron density of states, it is found that C5 F10 O and C3 F6 O bonded to the copper surface mainly by p orbitals on carbonyl oxygen atom and the pseudogaps are 3.2 eV and 2.5 eV. C2 F4 and CO bonded to the copper surface by sp hybrid orbitals of carbon atoms, with a pseudogap of about 4 eV. Based on the above analysis, it can be seen that C5 F10 O and its main decomposition products C3 F6 O, C2 F4 and CO have poor compatibility with metal copper.